Biofilm characterization and dynamic simulation of advanced rope media reactor for the treatment of primary effluent - Shewa, Wudneh A (Water environment research : a research publication of the Water Environment Federation, 2024)
© 2024 The Author(s). Water Environment Research published by Wiley Periodicals LLC on behalf of Water Environment Federation.